Stigma Masyarakat terhadap Penderita Covid-19 - Syntha Novita; Yunus Elon (Jurnal Kesehatan, 2021)
Covid-19 is a deadly disease that infects the respiratory system and can spread very quickly. The number of covid-19 cases that are increasing every day creates pressure on the community, which triggers the stigmatization of covid-19 sufferers. This study aims to analyze the stigma picture of society and see the relationship between stigma and public acceptance of covid-19 sufferers. This type of descriptive-analytic research with a quantitative approach. The subjects were 300 students studying at the Bandung city university who were selected using a non-probability technique with an incidental sampling approach. The instrument used was adopted and modified from the existing public acceptance questionnaire and tested the validity and reliability of 30 subjects with r table>,361 with a significance level of 5%, with a Cronbach alpha reliability ,794. The results of the univariate analysis showed that instrumental stigma was categorized as low 99 (33%), high 201 (67%), low symbolic stigma 134 (44,7%), high 166 (55,3%), low politeness stigma 241 (80,3%) ), high 59 (19,7%) and good public acceptance of 225 (75%) and poor 75 (25%). The results of the chi-square analysis showed a significant relationship with instrumental, symbolic, and modesty stigma towards public acceptance. The higher the instrumental stigma and symbolic stigma in society, the worse the public's acceptance of covid-19. Education regarding the prevention and spread of covid-19 and the importance of mental health during the covid-19 pandemic needs to be improved so that the public is not misinformed and the perceptions about covid-19.